Analysis of interface formation mechanism in GaN double-polarity selective-area growth by metalorganic vapor phase epitaxy. (1st April 2016) - Kuze, Kenta; Osumi, Noriyuki; Fujita, Yohei; Inoue, Yoku; Nakano, Takayuki
Abstract: The fabrication of quasi-phase-matching (QPM) crystals by selective-area growth on the two asymmetrically polar surfaces of GaN is examined. We attempted the fabrication of GaN-QPM crystals by one-time growth using a carbon mask. For GaN double-polarity selective-area growth (DP-SAG), we investigated the effect of varied nitriding times of the Al2 O3 templates patterned with the carbon mask. We optimized the nitriding conditions for the DP-SAG process, and evaluated the substrate fabricated by the optimized DP-SAG process. In addition, we examined the interface formation mechanism of DP-GaN fabricated by GaN DP-SAG process. We determined that it is possible to fabricate DP-GaN with a sharp interface by optimizing the growth conditions.